2017
DOI: 10.1097/md.0000000000008752
|View full text |Cite
|
Sign up to set email alerts
|

HPV types in cervical cancer tissue in South Africa

Abstract: Accurate identification of human papillomavirus (HPV)-types in cervical cancer tissue may be important for tailoring tests for primary screening and types to be included in a vaccine. The aim of this study was to compare test-performance of a 45-type HPV deoxyribonucleic acid (DNA)-test with a 9-type HPV messenger ribonucleic acid (mRNA)-test in cervical cancer tissues.In a case-series design 188 women with diagnosed cervical cancer during the period January 2008 to July 1, 2011 at the Gynaecological Oncology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The distribution of HPV genotypes and genera among the 348 patients with HPV-associated CC is shown in Table 1 , based on the hierarchical approach described by Rad et al [ 33 ]. One or more specific genotypes were identified in 331 CCs, whereas in 17 tumors, it was not possible to identify the specific HPV type(s).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of HPV genotypes and genera among the 348 patients with HPV-associated CC is shown in Table 1 , based on the hierarchical approach described by Rad et al [ 33 ]. One or more specific genotypes were identified in 331 CCs, whereas in 17 tumors, it was not possible to identify the specific HPV type(s).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings of high frequency of HPV-16 genotype infection as a single infection or in mixed infections with other HPV genotypes in HIV-1-positive women with cervical disease have been reported previously in different parts of the world, namely: Brazil, [ 14 ] Burkina Faso, and South Africa in 1 study with samples from the 2 countries, [ 50 ] Cameroon, [ 51 ] South Africa, [ 9 , 38 , 52 ] and the USA. [ 53 , 54 ] Three studies; 1 from Mozambique, [ 40 ] 1 from 2 countries Kenya and South Africa, [ 55 ] and 2 from South Africa, [ 56 ] did not find the association of HIV infection and HPV-16 genotype infection. However, 2 studies; the 1 from Kenya and South Africa, and the 1 from South Africa, used cervical swabs or brushes to collect cells/tissues around the cervix for HPV testing.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the two mRNA assays were utilized to evaluate test performance for detecting CIN3 disease and cervical cancer. Various combinations of HPV types, ranging from three (16,18,45) to eight (16,18,45,31,33,52,58,35), were assessed, and the subsequent impact on cervical cancer prevention was estimated based on the reported types detected in cervical cancer cases from the same hospitals [38]. The prevalence data presented by Rad et al allowed the estimation of the potential contribution of each HPV type to the development of cervical cancer.…”
Section: Analysis Of Mrna Assays and Cervical Cancer Prevention Poten...mentioning
confidence: 99%
“…In a prior investigation by Rad et al, the distribution of HPV types was examined in 159 women with confirmed cervical cancer and known HIV status. This cohort was drawn from the same hospitals involved in our present study [38]. Leveraging the reported South African prevalence data, we assessed the potential impact of various combinations of mRNA HPV types in primary cervical cancer screening.…”
Section: Impact On Cervical Cancer Preventionmentioning
confidence: 99%